An experimental study on a novel cold-formed steel connection for light gauge open channel steel trusses. (July 2016) - Ahmadi, Amin; Mathieson, Chris; Clifton, G. Charles; Das, Raj; Lim, James B.P.
Abstract: This paper describes an experimental investigation on a novel hollow connector, to be referred to as the Howick Rivet Connector (HRC). The HRC is of diameter of 12.75 mm and thickness of 0.95 mm and can be used to connect cold-formed steel channel-sections with a gap, such as found in the connection arrangement of cold-formed steel trusses and seismic framing units. Laboratory tests on twenty-seven Tee-stub specimens that use the HRC are described; for comparison, another twenty-seven Tee-stub specimens are also tested that use standard bolts. In the laboratory tests, the effect of three different thicknesses of channel-sections and three different end distances are investigated. It is shown that the behaviour of the HRC Tee-stubs is similar to that of the bolted Tee-stubs, but possess a higher capacity and an improved ductility, as shown by a longer yield plateau once the connection becomes inelastic. It recommended that a minimum end distance of 1.5 times the diameter of the HRC is sufficient. Design equations that can be used to predict the bearing strength of the HRC Tee-stubs are proposed; for these equations, the index of reliability calculated was greater than the recommended 3.5. Highlights: A novel form of connection for cold-formed steel open channel trusses that eliminate bolt-slip Twenty-seven Tee-stub tests using the novel form of connection and comparison with further twenty-seven Tee-stub tests using standard bolt. Design recommendations for bearing strength of the novel form of connection